Works of the Law and the Curse of the Law (Galatians 3.10–14) - Dunn, James D. G. (New Testament studies, 1985)
The two most recent studies of Paul and the law both show a large measure of agreement in criticizing Paul's treatment of the law as inconsistent and self-contradictory. E. P. Sanders argues that Paul's ‘break’ with the law gave rise to different questions and problems, and that his ‘diverse answers, when set alongside one another, do not form a logical whole’.1 So, in particular, Paul's ‘treatment of the law in chapter 2 (of Romans) cannot be harmonized with any of the diverse things which Paul says about the law elsewhere’; in Romans 2 ‘Paul goes beyond inconsistency or variety of argument and explanation to true self-contradiction’.2 More thoroughgoing is H. Räisänen, who can see only one way to handle what Paul says: ‘contradictions and tensions have to be accepted as constant features of Paul's theology of the law’.3 Again and again he finds himself driven to the conclusion that Paul contradicts himself. So, for example, with Rom 13. 8–10: ‘Paul seems here simply to have forgotten what he wrote in ch. 7 or in 10. 4’; ‘(Romans) 2.14–15,26–27 stand in flat contradiction to the main thesis of the section’; Paul puts forward ‘artificial and conflicting theories about the law’.4 The artificiality and tension is evident not least in Gal 3. 10–12, where Räisänen finds the argument of 3. 10 to be at odds with the argument of 3. 11–12.5